Analysis of the genomic termini of tupaia herpesvirus DNA by restriction mapping and nucleotide sequencing. - Albrecht, M (1985)
A recombinant plasmid harboring both genomic termini of tupaia herpesvirus (THV) DNA was characterized by restriction enzyme analysis and by determination of the nucleotide sequence. A unique NotI cleavage site was found that is located approximately 19 base pairs upstream of the THV terminal junction. THV DNA fragments from virion DNA were analyzed by using the same restriction enzymes as for the recombinant plasmid. The comparative fine mapping of virion THV DNA revealed heterogeneous molecules of variable lengths with the NotI cleavage site conserved. A number of short direct and inverted repeats and palindromes were found surrounding the THV terminal joint. The THV repetitive sequences were compared with the repeats reported for the DNA termini of herpes simplex virus, varicella-zoster virus, and Epstein-Barr virus and are discussed in respect to signals for a site-specific endonuclease required for packaging.